Effect of rotation speed and temperature to wax deposition for Malaysian crude oil - Fazerah, Moen (2015)
Wax depositions have been a major problem in the oil and gas field. It generates additional pressure drop and causes fouling which ultimately increase the operating cost during production, transportation, and handling of waxy crude oil. The problem are initiated due to the decrease of crude oil temperature during the transportation process which eventually caused the solidified of the crude oil to form wax. The deposited wax is normally removed by pigging process. The wax deposition of the crude oil in the pipeline makes the flow area smaller and smaller with time, which then influences the transportation capacity and the operation safety of the pipeline. There are many factors that influence the wax deposition: the crude components, the carbon atom distribution of the paraffin, the oil temperature, the temperature difference between the oil and the pipe wall, the deposition duration, the flow rate, and so on. In this research the effect of rotation speed was investigated toward the wax deposition. In addition, the temperature effect to the wax solubility is also been studied. The experimental work were conducted using cold finger device. Two different type of wax inhibitor are used in this study which are cyclohexane and toluene. As rotation speed is increased, the wax deposit obtained at the cold finger is decreased. However, at the certain minimum point, the amount of wax deposit is increased. For the wax solubility test, temperature was found to be the main effect to the wax. At the highest temperature, the solubility of paraffin wax is increased.